2021
DOI: 10.1140/epjs/s11734-021-00340-5
|View full text |Cite
|
Sign up to set email alerts
|

A dynamical map to describe COVID-19 epidemics

Abstract: Nonlinear dynamics perspective is an interesting approach to describe COVID-19 epidemics, providing information to support strategic decisions. This paper proposes a dynamical map to describe COVID-19 epidemics based on the classical susceptible-exposed-infected-recovered (SEIR) differential model, incorporating vaccinated population. On this basis, the novel map represents COVID-19 discretetime dynamics by adopting three populations: infected, cumulative infected and vaccinated. The map promotes a dynamical d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Linjunfeng [27] added 'invisible disseminator' on the traditional SEIR model and the results reflected the effective of nucleic acid detection and other technologies. Dos et al [28] proposed a dynamic map to describe the COVID-19 epidemic on the classical SEIR differential model with vaccinated population, which can describe three population dynamics: newly infected population, cumulative infected population and vaccinated population. The model has reduced the number of variables, made it easy to adjust parameters, and used analysis tools to define useful information.…”
Section: Study On the Covid-19 Spread With Improved Sir Modelmentioning
confidence: 99%
“…Linjunfeng [27] added 'invisible disseminator' on the traditional SEIR model and the results reflected the effective of nucleic acid detection and other technologies. Dos et al [28] proposed a dynamic map to describe the COVID-19 epidemic on the classical SEIR differential model with vaccinated population, which can describe three population dynamics: newly infected population, cumulative infected population and vaccinated population. The model has reduced the number of variables, made it easy to adjust parameters, and used analysis tools to define useful information.…”
Section: Study On the Covid-19 Spread With Improved Sir Modelmentioning
confidence: 99%
“…Their results show that for a certain set of parameters can be related to chaos. dos Reis and Savi [ 14 ] present a dynamical map to explain Covid-19 epidemics based on the standard susceptible-exposed-infected-recovered (SEIR) differential equations and incorporating the vaccinated population. Finally, Borah et al [ 15 ] revisit the past plague epidemic (India) and compare with the Covid-19 pandemic based on fractional-order chaotic models and fuzzy logic control.…”
Section: Covid-19 Modelingmentioning
confidence: 99%
“…[ 36 ] that in case roll out of vaccines are not upto speed, then permanent drug treatment should be focused on. Some other interesting models ([ 37 40 ]) on vaccination and prioritization have been reported in literature and it is concluded that vaccination is an efficient tool to stop the spread of infections.…”
Section: Introductionmentioning
confidence: 99%